Affirmative Action in Malaysia and South Africa : Preference for Parity - Lee, Hwok Aun (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Malaysia and South Africa implement the most extensive affirmative action programmes worldwide. This book explores why and how to effect preferential treatment which has been utilized in the pursuit of inter-ethnic parity, specifically in higher education, high-level occupations, enterprise development and wealth ownership. Through methodical and critical analyses of data on education, workforce and population, the book evaluates the primary objectives of increasing majority representation in education, employment, enterprise and ownership. The book also critically considers questions of the attainments and limitations of ethnic preferential treatment in reducing disparity, the challenges of developing capability and reducing dependency and the scope for policy reforms.
OCLC-licensed vendor bibliographic record.
Keywords: Affirmative action programs -- Malaysia; Affirmative action programs -- South Africa; BUSINESS & ECONOMICS / General